USE OF CONE-BEAM COMPUTED TOMOGRAPHY IN PEDIATRIC PATIENTS: A RETROSPECTIVE OBSERVATIONAL STUDY - Sevde Göksel; Ahmet Faruk Ertürk; Gülsevim Oda; Hülya Çakır Karabaş; İlknur Özcan (Sabiad)
Objectives: This study aimed to determine and classify the reasons for cone-beam computed tomography (CBCT) imaging requests in the Oral and Maxillofacial Radiology Department, Istanbul University Faculty of Dentistry, and to examine which reasons more commonly require CBCT imaging.Material and methods: From the local CBCT database, 956 pediatric patients gave their consent. Subsequently, age, gender, the reason for referral, a field of view (FOV), and referral departments were collected. Patients were grouped according to age distribution as 1-6 years, 7-12 years, and 13-17 years. Descriptive and comparative statistical analysis was performed.Results: When CBCT referral reasons were analyzed, some of the most common requests were bone pathology (26.25%), impacted teeth (19.87%), dental anomalies (14.12%), cleft lip, and palate (13.91%), respectively. When referral reasons are evaluated according to age groups, dentoalveolar trauma (p=0.049), impacted teeth (p=0.000), dental anomalies, surgical applications (p=0.021), bone pathology (p=0.004), cleft lip and palate statistically significant differences were found between the (p=0.000) indications and age groups (p=0.000).Conclusion: This study can guide dental practitioners in referring pediatric patients for three-dimensional imaging